2014
DOI: 10.1186/1471-2164-15-744
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome differences in the hypopharyngeal gland between Western Honeybees (Apis mellifera) and Eastern Honeybees (Apis cerana)

Abstract: BackgroundApis mellifera and Apis cerana are two sibling species of Apidae. Apis cerana is adept at collecting sporadic nectar in mountain and forest region and exhibits stiffer hardiness and acarid resistance as a result of natural selection, whereas Apis mellifera has the advantage of producing royal jelly. To identify differentially expressed genes (DEGs) that affect the development of hypopharyngeal gland (HG) and/or the secretion of royal jelly between these two honeybee species, we performed a digital ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
(36 reference statements)
4
33
0
Order By: Relevance
“…This is in accord with the general notion that mrjps are higher expressed in brood‐feeding nurse bees than in foragers (Klaudiny et al, ; Kubo et al, ; Ohashi et al, ). However, whereas all other mrjps do have their highest transcript abundance during the nurse bee period, mrjp6 shows highest abundance at day 20 (Table ) in accordance with previous studies reporting on a significantly higher expression of mrjp6 in forager compared to nurse bee heads and HGs (Buttstedt et al, ; Liu et al, ). In the brain, mrjp6 expression does not show any caste‐related modulation supported by Hernández et al () who did not detect differences in MRJP6 between brains of nurses and foragers.…”
Section: Discussionsupporting
confidence: 90%
“…This is in accord with the general notion that mrjps are higher expressed in brood‐feeding nurse bees than in foragers (Klaudiny et al, ; Kubo et al, ; Ohashi et al, ). However, whereas all other mrjps do have their highest transcript abundance during the nurse bee period, mrjp6 shows highest abundance at day 20 (Table ) in accordance with previous studies reporting on a significantly higher expression of mrjp6 in forager compared to nurse bee heads and HGs (Buttstedt et al, ; Liu et al, ). In the brain, mrjp6 expression does not show any caste‐related modulation supported by Hernández et al () who did not detect differences in MRJP6 between brains of nurses and foragers.…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that the relative expression levels of the SV2C, eIF-4E, PDK1, IMP, CGNP and TGF-βR1 genes were reduced from nurse to forager, which is consistent with our previous DGE analysis (Liu et al, 2014), suggesting that our previous DGE results are reliable.…”
Section: Discussionsupporting
confidence: 81%
“…Both the present study and our prior observation (Liu et al, 2014) suggested that the expression levels of eIF-4E, CGNP, IMP and TGF-βR1 expressing higher at newly emerged worker, nurse and reversed nurse stages compared to forager stage which is in parallel with the physiological conditions of HGs: the HGs grew rapidly at newly emerged worker stage and synthesized a large amount of royal jelly at the nurse stage, so many genes related to the biological metabolism and cell growth over expressed at these two stages and then reduced their expression quickly at forager stage in view of the degeneration of HGs and the cell apoptosis. However, the HGs re-growed and speeded up biological metabolism at reversed nurse stage lead to increased expression of many relevant genes.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations